Red emission, upconversion and intensity parameters of erbium oxide doped tellurite glass for laser glass - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2021)
Red emission, upconversion and intensity parameters of erbium oxide doped tellurite glass for laser glass by Muhammad Noorazlan Abd Azis